Monolithic Photoelectrochemical CO2 Reduction Producing Syngas at 10% Efficiency. Issue 21 (20th April 2021) - Kistler, Tobias A.; Um, Min Young; Cooper, Jason K.; Sharp, Ian D.; Agbo, Peter
Abstract: Increasing anthropogenic carbon dioxide emissions have prompted the search for photoelectrochemical (PEC) methods of converting CO2 to useful commodity products, including fuels. Ideally, such PEC approaches will be sustained using only sunlight, water, and CO2 as energetic and reactant inputs. However, low peak conversion efficiencies (<5%) have made commercialization of fully‐integrated PEC devices prohibitive. Here, a 4 cm 2 monolithic PEC device exceeding 10% solar‐to‐fuel efficiency with principal fuel products of carbon monoxide and hydrogen is reported. The corresponding solar‐to‐CO and solar‐to‐H2 efficiencies are 7% and 3.5%, respectively. Screening of a range of operating conditions reveals a tunable product mixture of H2 and CO using a gold electrocatalyst. Accordingly, it is shown that device optimization yields a H2 ‐to‐CO ratio of 1:2 commonly present in synthesis gas (syngas). Notably, the modularity and facile fabrication of this device permit the incorporation of a broad array of materials for various applications. For example, the electrocatalyst may easily be swapped to target a different set of products. Abstract : Photoelectrochemical conversion of carbon dioxide into fuels and chemicals is an appealing method to combat rising CO2 concentrations in the atmosphere. A modular, fully‐integrated device architecture is presented, following design principles developed for dark electrolysis. The result is a compact device, allowing for efficient and stable conversion of water and CO2 into carbon monoxide and hydrogen (synthesis gas).